Antifungal Potential of Copper(II), Manganese(II) and Silver(I) 1,10-Phenanthroline Chelates Against Multidrug-Resistant Fungal Species Forming the Candida haemulonii Complex: Impact on the Planktonic and Biofilm Lifestyles - Gandra, Rafael M.; Mc Carron, Pauraic; Fernandes, Mariana F.; Ramos, Lívia S.; Mello, Thaís P.; Aor, Ana Carolina; Branquinha, Marta H.; McCann, Malachy; Devereux, Michael; Santos, André L. S. (Frontiers in Microbiology, 2017)
Candida haemulonii, Candida haemulonii var. vulnera and Candida duobushaemulonii, which form the Candida haemulonii complex, are emerging etiologic agents of fungal infections known to be resistant to the most commonly used antifungals. The well-established anti-Candida potential of metal complexes containing 1,10-phenanthroline (phen) ligands encouraged us to evaluate different copper(II), manganese(II) and silver(I) phen chelates for their ability to inhibit planktonic growth and biofilm of C. haemulonii species complex. Two novel coordination complexes, {[Cu(3,6,9-tdda)(phen)2].3H2O.EtOH}n and [Ag2(3,6,9-tdda)(phen)4].EtOH (3,6,9-tddaH2=3,6,9-trioxaundecanedioic acid), were synthesized in a similar fashion to the other, previously documented, sixteen copper(II), manganese(II) and silver(I) chelates employed herein. Three isolates of each C. haemulonii species complex were used and the effect of the metal chelates on viability was determined utilizing the CLSI standard protocol and on biofilm-growing cells using the XTT assay. Cytotoxicity of the chelates was evaluated by the MTT assay, employing lung epithelial cells. The majority of the metal chelates were capable of interfering with the viability of planktonic-growing cells of all the fungal isolates. The silver complexes were the most effective drugs (overall geometric mean of the minimum inhibitory concentration (GM-MIC) ranged from 0.26 to 2.16 µM), followed by the manganese (overall GM-MIC ranged from 0.87 to 10.71 µM) and copper (overall GM-MIC ranged from 3.37 to >72 µM) chelates. The manganese chelates (CC50 values ranged from 234.51 to >512 µM) were the least toxic to the mammalian cells, followed by the silver (CC50 values ranged from 2.07 to 13.63 µM) and copper (CC50 values ranged from 0.53 to 3.86 µM) compounds. When tested against mature biofilms, the chelates were less active, with MICs ranging from 2- to 33-fold higher levels when compared to the planktonic MIC counterparts. Importantly, manganese(II), copper(II) and silver(I) phen chelates are relatively cheap and easy to synthesize and they offer significant antifungal chemotherapeutic potential for the treatment of highly resistant pathogens.